Traktat Lizboński a wspólnotowe wartości europejskie - Banaszak, Maciej (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
An issue raised more and more frequently in political, as well as scientific discourse in the context of the European Union, is “democratic deficit”. At the time, EU is perceived as an institution guaranteeing the preservation of democratic values in Europe and promoting them both on the continent and beyond. This article discusses both points of view, with emphasis placed on the democratic deficit aspect, measures undertaken to eliminate the negative consequences of the process, as well as the history of the concept: starting from the single European Act, through general elections to the European Parliament, and formal solutions leading to the gradual increase of EU powers. It is assumed in the article that the problem of democratic deficit has persisted in the European Union, especially since several changes were introduced to the political system of EU after The Treaty of Lisbon. As result, the key question that must be answered is whether under the provisions of the Treaty the EU will strengthen its democratic legitimacy. This article attempts to provide an answer, analyzing the role of national parliaments in the new institutional and normative reality and in the context of the democratic legitimacy deficit.